Pengaruh Flexible Working Arrangements terhadap Work Life Balance, dan Kinerja Pegawai dengan Kepuasan Kerja sebagai Mediator : Studi Kasus pada Kementerian Lingkungan Hidup dan Kehutanan - Atsarina Silminawati; Riani Rachmawati (LITERATUS, 2022)
Flexible work arrangements have become a new thing in government agencies due to the Covid-19 pandemic. So this study was conducted to see the effect of flexible work arrangements on work life balance, job satisfaction and employee performance in government agencies, especially the Ministry of Environment and Forestry. And by considering the mediating factor of job satisfaction in the relationship of flexible work arrangements with work-life balance and the relationship of flexible work arrangements with employee performance. This research is a quantitative research by conducting an online survey. Respondents in this study were employees of the Ministry of Environment and Forestry, especially at the central level as many as 222 employees. The research hypotheses were tested using Structural Equation Modeling (SEM) analysis techniques. The results showed that there was a significant effect between flexible work arrangements, job satisfaction, and employee performance. Job satisfaction also has a significant effect on work-life balance and employee performance. In addition, job satisfaction was found to be a mediator between the effects of flexible work arrangements and work-life balance, and flexible work arrangements and employee performance.